Ameliorative effects of Berberine chloride against 5-fluorouracil-induced cardiotoxicity in Sprague Dawley rats - Mirna Akram Labib; Omar S. Saeed; Samar H. ElSharkawy; Marwa S. Khattab; Hesham Y. El-Zorba; Khaled Abo-EL-Sooud (Scientific Reports)
Abstract 5-Fluorouracil (5-FU) is the most commonly used chemotherapeutic agent for solid malignancies. Although it has crucial therapeutic effects, it ranks as the second most cardiotoxic antineoplastic agent. Berberine (BBR) is a quaternary benzylisoquinoline alkaloid with promising antioxidant properties. The current study aimed to assess the palliative effect of BBR on 5-FU-induced cardiotoxicity in rats. Fifty male Sprague Dawley rats were randomly divided into five groups: negative control, which received 2% DMSO orally (PO) for 2 weeks; cardiotoxic, which received a single intraperitoneal (IP) injection of 5-FU (150 mg/kg); groups 3 and 4, which received a single IP injection of 5-FU (150 mg/kg) followed by BBR (50 mg/kg and 100 mg/kg, respectively) PO for 2 weeks; and a BBR-only group, which received BBR (100 mg/kg) PO for 2 weeks. On the 14th day, all groups underwent ECG evaluation. Blood and heart samples were collected 24 h after the last dose for further investigations. 5-FU induced significant alterations in the ECG pattern and caused a significant increase in cardiac troponin I (cTnI), creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), and malondialdehyde (MDA). Moreover, it led to decreased levels of superoxide dismutase (SOD), reduced glutathione (GSH), and total antioxidant capacity (TAC). Our data suggest that BBR could mitigate 5-FU-induced cardiotoxicity by modulating cardiac injury markers, normalizing cTnI, CK-MB, and LDH levels, reducing oxidative stress by lowering MDA levels, and increasing SOD, GSH, and TAC levels. Additionally, BBR inhibited apoptotic events by suppressing caspase-3 activation and upregulating Bcl-2 expression, reduced the inflammatory response by downregulating cyclooxygenase-2 (COX-2) and tumor necrosis factor-alpha (TNF-α) expression levels, and decreased the risk of thrombosis by increasing endothelial nitric oxide synthase (eNOS) expression levels. In conclusion, BBR exerts ameliorative effects against 5-FU-induced cardiotoxicity in rats.